Global scientific performance and research trends of the interrelation between climate change and economic growth - Lobonț Oana-Ramona; Varadi Ana-Elena; Vătavu Sorana; Tao Ran; Moldovan Nicoleta Claudia (BIO Web of Conferences)
This paper conducts a comprehensive bibliometric analysis to explore the existing literature on the interrelation between climate change and economic growth through the prism of environmental policies. Utilising both VOSviewer and Bibliometrix software, we analyse 2,131 articles from the Web of Science database between 2000 and 2024, focusing on the fields of Economics, Social Sciences, and Environmental Science. Our investigation identifies key trends, research hotspots, patterns, and gaps in the literature, highlighting the significant impact of climate change on the macroeconomic environment. Bibliometric networks created on account of keywords such as “climate change risks,” “macroeconomy,” and “environmental policy” reveal strong interconnections among research clusters, particularly emphasising the role of public policy in managing climate-related risks. Notably, our findings evidence the geographical distribution of research on this topic, which is more prominent in non-EU countries despite the European Union’s recent policy focus on sustainability. This paper underscores the necessity for targeted research and policy measures to address the economic implications of climate change, emphasising the role of consumer behaviour, uncertainty, and expectations with a country-specific focus. Our research contributes to the existing literature by providing a detailed mapping of the intellectual landscape and suggesting directions for future research to support effective climate policies.